2020
DOI: 10.1039/d0cp01858a
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of an opto-chemical “neurocomputer”

Abstract: A hierarchical network of pulse coupled chemical micro-oscillators and excitable cells demonstrates intelligent behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
(48 reference statements)
0
18
0
Order By: Relevance
“…Another similar concept is that of volume transmission and intercellular communication via diffusing signaling molecules secreted by excitable cells (Sykova and Nicholson, 2008). There also appears to be an interesting connection between the self-organizing Ca 2+ signaling in coupled astrocytes and the concept of "reaction-diffusion computing" or "chemical computing" based on oscillatory chemical (e.g., Belousov-Zhabotinsky) systems in coupled reactor volumes, e.g., microemulsions (Adamatzky et al, 2005;Epstein et al, 2012;Showalter and Epstein, 2015;Torbensen et al, 2017;Vanag, 2019;Proskurkin et al, 2020). It is conceivable that astrocytes can provide a substrate for such Ca 2+ -based reaction-diffusion computing in parallel to, and organizing sparse network-based neuronal connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Another similar concept is that of volume transmission and intercellular communication via diffusing signaling molecules secreted by excitable cells (Sykova and Nicholson, 2008). There also appears to be an interesting connection between the self-organizing Ca 2+ signaling in coupled astrocytes and the concept of "reaction-diffusion computing" or "chemical computing" based on oscillatory chemical (e.g., Belousov-Zhabotinsky) systems in coupled reactor volumes, e.g., microemulsions (Adamatzky et al, 2005;Epstein et al, 2012;Showalter and Epstein, 2015;Torbensen et al, 2017;Vanag, 2019;Proskurkin et al, 2020). It is conceivable that astrocytes can provide a substrate for such Ca 2+ -based reaction-diffusion computing in parallel to, and organizing sparse network-based neuronal connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, fast oscillations are promising because they speed up of information processing. To compare with existing systems, optochemical neurocomputer [27] using BZ droplets in rubber tubings and light coupling has one of the natural pulses generator 75 s and 82 s, the rest of the droplets are susceptible to forced period of pulses. The working cycle of the optochemical neurocomputer is over an hour [27].…”
Section: Discussionmentioning
confidence: 99%
“…To compare with existing systems, optochemical neurocomputer [27] using BZ droplets in rubber tubings and light coupling has one of the natural pulses generator 75 s and 82 s, the rest of the droplets are susceptible to forced period of pulses. The working cycle of the optochemical neurocomputer is over an hour [27]. Another system is programmable chemical computer for pattern recognition, which works with periods 30 s to 60 s in an array of BZ droplets [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that an oscillating BZ-reaction can be efficiently applied for information processing Smelov and Vanag (2018) ; Vanag VK. (2019) ; Proskurkin et al (2020) ; Egbert, (2019) ; Duenas-Diez and Perez-Mercader (2019) ; Duenas-Diez and Perez-Mercader (2020) . For example, it has been shown that a network of interacting chemical oscillators can be trained to perform classification tasks with a reasonable accuracy Gruenert et al (2015) ; Gizynski and Gorecki (2017a) .…”
Section: Introductionmentioning
confidence: 99%